Preservação da fertilidade com o uso do agonista de GnRH em mulheres submetidas à quimioterapia para tratamento de linfoma: revisão sistemática com metanálise - Janaina Campos Senra (2016)
Introduction: Hodgkin lymphoma is the most prevalent cancer in young people of childbearing age. In recent decades, the introduction of new chemotherapeutic agents and combination regimens brought about increased survival and cure rates for this disease. On the other hand, concerns about post cure side effects and life quality have been discussed. Ovarian damage is one of the main consequences of chemotherapy and has variable clinical presentation, ranging from transient to permanent amenorrhea, infertility or early menopause. As the cytotoxic effect is greater in dividing cells such as the ovarian granulosa and theca cells, it is believed that keeping them at rest may reduce their susceptibility to these deleterious effects. The GnRH agonist, through inhibition of the hypothalamic-pituitary-ovarian axis, keeps the gonads inactivated. Several preclinical animal studies and phase II studies have observed the benefit of this intervention. However, phase III studies showed conflicting results as well as meta-analyzes that attempted to synthesize them. Objective: To evaluate the effectiveness of GnRH agonist before and during chemotherapy in premenopausal women with lymphoma for the protection of ovarian reserve. Methods: Electronic search was conducted until August 2014 in CENTRAL databases, LILACS, MEDLINE and ClinicalTrials.gov. Only randomized clinical trials comparing concurrent use of GnRH analogue plus chemotherapy with chemotherapy alone were eligible. Two reviewers analyzed, independently, the inclusion criteria, bias risk and extracted data from included studies. Any disagreements were addressed and resolved between both reviewers. Results: The search identified 171 articles and only 3 of these were included. They evaluated the rate of premature ovarian failure (POF) and pregnancy rate after treatment. Only two studies described have Anti-Müllerian hormone (AMH) dosages as a marker of ovarian reserve. There was no statistical difference in FOP rate between the control and intervention groups (RR 0.83, 95% CI 0.24 to 2.88), as well as pregnancy rate at follow-up (RR 0.77, CI 95% 0,19- 3,15). The analysis with intention-to-treat (ITT) found similar results, except for a slight decrease in pregnancy rate in the intervention group when including the number of patients originally allocated in the denominators and added the loss of control in the numerator of the same group. This outcome, however, has no clinical relevance, since the strategy used to calculate ITT intends to avoid overestimating positive results and it is difficult to measure its interference in the negative one. There was no statistical difference in AMH measurement in follow-up between the control and intervention groups (RR 0.54, 95% CI -0.31 - 1.38). The sensitivity analysis reproduced the same results, confirming that all included studies bore the same weight statistically. Conclusion: Our evidence suggests that the use of GnRH agonist during chemotherapy in patients with lymphoma does not reduce the incidence of premature ovarian failure. Neither does it increase the chances of future spontaneous pregnancy or maintain adequate AMH levels. Therefore, it should not be used in these cases and should not replace proven techniques of fertility preservation such as gamete and embryo vitrification. However, the interpretation of results must be carried out with caution, since the randomized studies that are available have mostly been done with small samples of patients, are heterogeneous and have short follow-ups. Further good quality studies, controlled, randomized, with better parameters of ovarian reserve before and after treatment, longer follow-ups, correction for age and confusing factors and more robust samples are needed to improve the reliability of the current results.